EVALUATION OF CYTOTOXICITY AND EXPRESSION OF CASPASE-3 AND P53 IN HCT-116 CELLS OF LINEAGE TREATED WITH DIFFERENT EXTRACTS OF Euphorbia tirucalli L. - Archanjo, Anderson Barros; Careta, Francisco de Paula; Costa, Adilson Vidal; Nunes, Louisiane de Carvalho (Archives of Veterinary Science, 2016)
Euphorbia tirucalli, a plant commonly known as aveloz, has been employed in anticancer therapy with little scientific proof. The goal of this study was to evaluate the cytotoxic potential and expression of caspase-3 and p53 in colorectal cancer cell lines treated with aveloz extracts. Hexanic and hydroalcoholic extracts were prepared in different concentrations. After 96 h, cell viability and apoptosis rate (p53 and caspase-3 expression) were verified. The hexanic extract revealed higher cytotoxicity on HCT-116 cell line at concentrations above 125 µg/mL, and hydroalcoholic extract above 500 µg/mL. LC50 for the hexanic extract was 60.2873 µg/mL, and for hydroalcoholic extract 100.6066 µg/mL. There were significant differences among the averages of cells marked with p53 at the concentrations 62.5, 250 and 500 µg/mL, as well as among the averages of caspase-3-positive cells at the concentrations 62.5, 125 and 500 µg/mL, with higher cytotoxic effect being observed for the hydroalcoholic extract. The obtained data provides evidence for the cytotoxic potential in vitro of the hydroalcoholic and hexanic extracts of aveloz on HCT-116 cell line. There was an increase in the expression of caspase-3 and p53 in the tumor line cells exposed to extracts of E. tirucalli.